Interactive Effect of Phosphorus Fertilization and Rhizobial Inoculation on Symbiotic and Growth Potential of Selected Chickpea Cultivars - K SWARNALAKSHMI; S GOPALAKRISHNAN; M SINGH; V POONIYA; V SRINIVAS; SK CHATURVEDI (Seed Research, 2026)
The main aim of this study was to evaluate the effect of rhizobia and di-ammonium phosphate (DAP) on nodulation and plant growth-promotion (PGP) traits of chickpea cultivars under field conditions at IARI, New Delhi and ICRISAT, Patancheru during the Rabi season of 2014-15. Two chickpea cultivars, JAKI 9218 and Shubhra, were used in common by both the institutes, while the third cultivar varied; IARI used PUSA 372, whereas ICRISAT used JG11, popular variety of the respective locations. The seeds were subjected to four treatments, including T1 = positive control (only DAP); T2 = only rhizobia; T3 = rhizobia and DAP; and T4 = absolute control (no rhizobia and DAP). Manual planting was done in split plot design with three replications. Observations, including nodule number, nodule weight, shoot weight, root weight, pod weight, pod number, grain yield, stover yield, N and P uptake from shoots were recorded. Seed inoculation with rhizobia (T, and T₂) significantly enhanced nodulation and growth over un-inoculated controls (T₁ and T₁) at both IARI and ICRISAT locations. Among T₂ and T3, nodule weight observed was more in T3 than T₂ at both IARI and ICRISAT locations, except in case of one cultivar (Subhra) at ICRISAT where T₂ was significantly higher than T, Among the cultivars, Subhra was found to be more compatible to rhizobial strains used in this study than the other two cultivars at both the locations. At crop maturity stage, data were collected only at ICRISAT location due to hostile weather conditions at IARI. At ICRISAT, T3 recorded significantly higher shoot weight (up to 25%), pod weight (up to 37%), pod number (up to 16%), grain yield (up to 25%), stover yield (up to 8%) and P uptake (up to 10%) over T, the absolute control. It can be concluded that rhizobial strains in combination with DAP supports not only nodulation potential of chickpea but also its PGP traits.